Gerakan Anti Korupsi dan Restrukturisasi Gaji Pegawai Negeri - Achmad Zainuri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
The momentum and fervor in combating corruption currently underway cannot be separated from the green light and political will provided by President Susilo Bambang Yudhoyono (SBY). In the previous period, anti-corruption efforts were half-hearted and sluggish because some high-profile corruption suspects received protection from powerful individuals, resulting in their cases stagnating. For example, the case of Abdullah Puteh was only expedited after President SBY allowed the Governor of NAD to be questioned. Similarly, cases involving several regents, mayors, and members of regional councils in various areas could only be seriously investigated after President SBY granted permission, as the examination of state officials must be authorized by the president. However, the determination in the legal process of combating corruption must be carried out by professional human resources, supported by adequate salaries and welfare. Therefore, the fight against corruption cannot be separated from the restructuring of employee salaries, resulting in more effective anti-corruption measures.